Morphological Traits of the Radula in Viviparidae (Mollusca, Caenogastropoda) as a Master Key to Discrimination of Closely Related Species - Anistratenko, V.V.; Ryabceva, Yu.S.; Degtyarenko, E.V. (Вестник зоологии, 2013)
The radula morphology and variability in four European species of the family Viviparidae viz. Viviparus viviparus (Linnaeus, 1758), V. sphaeridius (Bourguignat, 1880), V. ater (Cristofori et Jan, 1832) and Contectiana listeri (Forbes et Hanley, 1853) were examined using scanning electron microscopy (SEM). Statistical methods reveal a certain value of rachidian tooth dimensional parameters as an efficient tool for taxonomy and discrimination of closely related species of the family.